Characterization of memory T cell subsets and common γ−chain cytokines in convalescent COVID-19 individuals. Issue 1 (8th March 2022) - Rajamanickam, Anuradha; Pavan Kumar, Nathella; Pandiaraj, Arul Nancy; Selvaraj, Nandhini; Munisankar, Saravanan; Renji, Rachel Mariam; Venkataramani, Vijayalakshmi; Murhekar, Manoj; Thangaraj, Jeromie Wesley Vivian; Muthusamy, Santhosh Kumar; Chethrapilly Purushothaman, Girish Kumar; Bhatnagar, Tarun; et al.
Abstract: T cells are thought to be an important correlates of protection against SARS-CoV2 infection. However, the composition of T cell subsets in convalescent individuals of SARS-CoV2 infection has not been well studied. The authors determined the lymphocyte absolute counts, the frequency of memory T cell subsets, and the plasma levels of common γ−chain in 7 groups of COVID-19 individuals, based on days since RT-PCR confirmation of SARS-CoV-2 infection. The data show that both absolute counts and frequencies of lymphocytes as well as, the frequencies of CD4 + central and effector memory cells increased, and the frequencies of CD4 + naïve T cells, transitional memory, stem cell memory T cells, and regulatory cells decreased from Days 15–30 to Days 61–90 and plateaued thereafter. In addition, the frequencies of CD8 + central memory, effector, and terminal effector memory T cells increased, and the frequencies of CD8 + naïve cells, transitional memory, and stem cell memory T cells decreased from Days 15–30 to Days 61–90 and plateaued thereafter. The plasma levels of IL-2, IL-7, IL-15, and IL-21—common γc cytokines started decreasing from Days 15–30 till Days 151–180. Severe COVID-19 patients exhibit decreased levels of lymphocyte counts and frequencies, higher frequencies of naïve cells, regulatory T cells, lower frequencies of central memory, effector memory, and stem cell memory, and elevated plasma levels of IL-2, IL-7, IL-15, and IL-21. Finally, there was a significant correlation between memory T cell subsets and common γc cytokines. Thus, the study provides evidence of alterations in lymphocyte counts, memory T cell subset frequencies, and common γ−chain cytokines in convalescent COVID-19 individuals. Graphical Abstract: Our study provides evidence of alterations in lymphocyte counts, memory T cell subset frequencies and common γ-chain cytokines in convalescent COVID-19 individuals.